LINDHO - use of the object oriented programming paradigm for hardware description and simulation - Brito Ferrari, Antonio de; Veloso, Aires (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes LINDHO, an object-oriented hardware description language supporting the description at the higher levels of abstraction, in particular at the architectural level. LINDHO, a much simpler and smaller language than VRDL, is based on C++, easy to be learned by electronic and computer engineers, and has expressive powers not inferior to VHDL. The language is presented informally through examples that try to convey its potential.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka